Pengaruh Informasi Akuntansi Dan Praktik Akuntansi Manajemen Terhadap Kinerja UMKM Di Kabupaten Gresik Jawa Timur - Kurnia Ulva Erlinasari; Khoirul Abidin (LPPM Universitas Wijaya Kusuma Surabaya, 2024)
Micro, Small and Medium Enterprises are one of the economic sectors that play an important role in Indonesia. The diversity of the scope of accounting information, management accounting practices and performance achievements of Micro, Small and Medium Enterprises (MSMEs), is a pictures that reflects the business of this sector. This is what encourages researchers to analyze more deeply the influence of accounting information and management accounting practices on the performance of MSMes in Gresik district, East Java. This study uses multiple regression analysis, with a population of all MSMEs in Gresik with food and beverage business types as many as 115. The sample used in this study was 55 Micro, Small and Medium Enterprises, which were determined using the solvin formula. The results of the study together revealed that the researcher’s model was empirically proven fit to explain the dependent variable. The results of the hypothesis test revealed that accounting information and management accounting practices both have a positive effect on the performance of MSMEs